90=2x*3x+1+5*5

Simple and best practice solution for 90=2x*3x+1+5*5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 90=2x*3x+1+5*5 equation:


Simplifying
90 = 2x * 3x + 1 + 5 * 5

Reorder the terms for easier multiplication:
90 = 2 * 3x * x + 1 + 5 * 5

Multiply 2 * 3
90 = 6x * x + 1 + 5 * 5

Multiply x * x
90 = 6x2 + 1 + 5 * 5

Multiply 5 * 5
90 = 6x2 + 1 + 25

Reorder the terms:
90 = 1 + 25 + 6x2

Combine like terms: 1 + 25 = 26
90 = 26 + 6x2

Solving
90 = 26 + 6x2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x2' to each side of the equation.
90 + -6x2 = 26 + 6x2 + -6x2

Combine like terms: 6x2 + -6x2 = 0
90 + -6x2 = 26 + 0
90 + -6x2 = 26

Add '-90' to each side of the equation.
90 + -90 + -6x2 = 26 + -90

Combine like terms: 90 + -90 = 0
0 + -6x2 = 26 + -90
-6x2 = 26 + -90

Combine like terms: 26 + -90 = -64
-6x2 = -64

Divide each side by '-6'.
x2 = 10.66666667

Simplifying
x2 = 10.66666667

Take the square root of each side:
x = {-3.265986324, 3.265986324}

See similar equations:

| -8(3b+2)+(25b-9)=0 | | (23y^2+4y^3-12)-(11y^3-8y^2+y)= | | 3.1q-2.2-5.3q=-3.2q-1.2 | | 9+x^2=0 | | 39=x+5 | | 2.2q-4.7-4.5q=3.3q-3.7 | | 39=x+5*3 | | (2z+5c-3a)-(6a+2c-4z)= | | -3(x+4)+13=-2x-11 | | (y-z-b)-(b+y+z)= | | (7262x)+(1.26a)-(2844x-8.23a)= | | 2x^5+7x^4-10x^3-53x^2-28x+28= | | (72.62x)+(1.26a)-(2844x-8.23a)= | | 8(2x-9)=2(8x+6) | | 3x^3=32 | | 9+11z-3=5z+69-3z | | -3(x-1)-7=4x-11 | | 18+3y=9y | | (24.2x)+(8.25)+(83.6x-2.92)= | | 4x=28-0.25(4-16x) | | 5n-6(n+2)=14 | | -8(3x-4)+1=15 | | 5s+3s=56 | | (2x+6a)-(4x-a)= | | 8x=14-0.5(10x+2) | | 2z=-10 | | 61=16+5(x-3) | | 4.2q-5.9-5.5q=-2.3q-3.6 | | 8p=2(p+9) | | 8(w-2)= | | 100.39=28.90+49.99+2x | | (2x+5)+(x-2)= |

Equations solver categories